Quantitative gaschromatographische / massenspektrometrische Bestimmung der Pentaerithrityltetranitrat-Metaboliten Pentaerithrityltrinitrat, Pentaerithrityldinitrat und Pentaerithritylmononitrat in Humanplasma - Schütz, Andrea; Kötting, Jochem; Epple, Franz; Ziegler, Ronald; Maier-Lenz, Herbert; Stalleicken, Dirk (Arzneimittelforschung, 1999)
Quantitative Gas Chromatographic/Mass Spectroscopic Determination of the Pentaerithrityltetranitrate Metabolites Pentaerithrityltrinitrate, Pentaerithrityldinitrate and Pentaerithritylmononitrate in Human PlasmaAssay methods based on gas chromatography/mass spectroscopy (GC-MS) may be used to measure PE1N (pentaerithrityl mononitrate, CAS 1607-00-7), PE2N (pentaerithrityl dinitrate, CAS 1607-01-8) and intermediate pentaerithrityltrinitrate (PE3N, CAS 1607-17-6) in human plasma. Based on this method a simplified method to quantify the metabolites of PETN (pentaerithrityl tetranitrate, CAS 78-11-5, Pentalong®) is described.In the present study a consistent method to extract the metabolites of human plasma and following derivatisation is described. Since PE1N can be quantified up to 150 ng/ml, PE2N and PE3N up to 30ng/ml in human plasma, a dilution of the plasma samples can be avoided.The mean recovery rate is not so high as in other described methods, and inaccuracy is about 10%. Therefore a calibration range between 0.2−30ng/ml of PE2N and 1−150ng/ml of PE1N has to be considered.The described method offers an alternative and applicable option to quantify the PETN- metabolites and elucidate their part as NO-donors.
Keywords: CAS 78-11-5; CAS 1607-00-7; CAS 1607-01-8; CAS 1607-17-6; Pentaerithrityltrinitrate, assay methods, metabolites; Pentalong®